2012
DOI: 10.1179/1465312512z.00000000022
|View full text |Cite
|
Sign up to set email alerts
|

What you need to know about bisphosphonates: an overview and general recommendations for orthodontic treatment

Abstract: The orthodontic treatment of patients on bisphosphonates is becoming an increasing aspect of contemporary practice. This article will draw attention to the chemical structure and effects of these drugs on bone and will provide the latest recommendations to avoid potential sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…9 This study also showed that two-thirds of the practicing dentists are aware of the dental interventions that might be troubled by Bps therapy such as; oral surgery, periodontal therapy, and orthodontics. The awareness rate reported here was higher than that reported by dentists in South Korea (56.5%) (10,11), in Canada (60%) (12)(13)(14)(15)(16) and physicians in Saudi Arabia (31%) (17,18) . Dentoalveolar surgery may cause or exacerbate an existing BRONJ in patients during or after Bps therapy.…”
Section: Discussioncontrasting
confidence: 70%
“…9 This study also showed that two-thirds of the practicing dentists are aware of the dental interventions that might be troubled by Bps therapy such as; oral surgery, periodontal therapy, and orthodontics. The awareness rate reported here was higher than that reported by dentists in South Korea (56.5%) (10,11), in Canada (60%) (12)(13)(14)(15)(16) and physicians in Saudi Arabia (31%) (17,18) . Dentoalveolar surgery may cause or exacerbate an existing BRONJ in patients during or after Bps therapy.…”
Section: Discussioncontrasting
confidence: 70%
“…Recent guidelines does not exclude patients treated with BPs from orthodontic treatment especially those taking low-doses ( 8 ). Although, a recent study consider patient taking high doses of BPs at high risk of MRONJ and the patient physician should be included in the decision of beginning orthodontic treatment ( 9 , 10 ). Informing the patient for the risk of developing a side effect such us MRONJ is of great importance ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a non-invasive dental treatment, orthodontics is classified as an elective treatment and it is thus considered a possible , in absence of MRONJ cases published related to it. However, it has been suggested that orthodontic movements, which cause an increase in alveolar bone remodeling, in the cancer patients in-treatment may encourage the accumulation of drugs in the jawbone [ 38 40 ]. However, it must be underlined that cancer patient being treated with ONJ-related drugs will rarely request orthodontic treatment [ 14 , 16 , 39 , 40 ].…”
Section: Cancer Patients In Treatment Phasementioning
confidence: 99%